Se-decorated SnO2/rGO composite spheres and their sodium storage performances - Zhang, Peng; Cao, Bin; Soomro, Razium A.; Sun, Ning; Xu, Bin (Chinese chemical letters, 2021)
A unique pomegranate-like SnO2/rGO/Se spheres were fabricated using a simple one-pot spray pyrolysis method to promote fast ion-transportation and alleviate the cycling volume variation of SnO2 when used as an anode material for sodium-ion batteries. [Display omitted] SnO2 is considered a promising anode material for sodium-ion batteries due to its high theoretical capacity and low cost. However, the poor electrical conductivity and dramatic volume variation during charge/discharge cycling is a major limitation in its practical applicability. Here we propose a simple one-pot spray pyrolysis process to construct unique pomegranate-like SnO2/rGO/Se spheres. The ideal structural configuration of these architectures was effective in alleviating the large volume variation of SnO2, besides facilitating rapid electron transfer, allowing the devised anode to exhibit superior sodium storage performances in terms of capacity (506.7 mAh/g at 30 mA/g), cycle performance (397 mAh/g after 100 cycles at 50 mA/g) and rate capability (188.9 mAh/g at an ultrahigh current density of 10 A/g). The experimental evidence confirms the practical workability of p-SnO2/rGO/Se spheres in SIBs.